It is a special function, which contains algebraic, trigonometric and exponential functions in terms of a variable $x$. So, the limit of the function should be simplified to our known form of exponential and trigonometric limit rules to solve this limit problem.

The numerator contains two exponential functions and a trigonometric function. Write the exponential functions closer to simplify them.

$\displaystyle \large \lim_{x \to 0}{\normalsize \dfrac{e^{3\displaystyle+x}-e^3-\sin{x}}{x}}$

The exponent of the first exponential term is a sum of $3$ and variable $x$. It can be written as product of two exponential terms by the product rule of exponents.

$= \,\,\,$ $\displaystyle \large \lim_{x \to 0}{\normalsize \dfrac{e^3 \times e^{\displaystyle x}-e^3-\sin{x}}{x}}$

$e^3$ is a common factor in the first two terms of the numerator. So, take $e^3$ common from them.

$= \,\,\,$ $\displaystyle \large \lim_{x \to 0}{\normalsize \dfrac{e^3{(e^{\displaystyle x}-1)}-\sin{x}}{x}}$

$= \,\,\,$ $\displaystyle \large \lim_{x \to 0}{\normalsize \Bigg[\dfrac{e^3{(e^{\displaystyle x}-1)}}{x}-\dfrac{\sin{x}}{x}\Bigg]}$

As per subtraction rule of limits, the limit of subtraction of two functions is equal to subtraction of their limits.

$= \,\,\,$ $\displaystyle \large \lim_{x \to 0}{\normalsize \dfrac{e^3{(e^{\displaystyle x}-1)}}{x}}$ $-$ $\displaystyle \large \lim_{x \to 0}{\normalsize \dfrac{\sin{x}}{x}}$

Now, find the limit of product of exponential functions but $e^3$ is a constant function. So, use constant multiple rule of limit for the product of constant and function to simplify the first term.

$= \,\,\,$ $e^3 \displaystyle \large \lim_{x \to 0}{\normalsize \dfrac{e^{\displaystyle x}-1}{x}}$ $-$ $\displaystyle \large \lim_{x \to 0}{\normalsize \dfrac{\sin{x}}{x}}$

$= \,\,\,$ $e^3 \displaystyle \large \lim_{x \to 0}{\normalsize \dfrac{e^{\displaystyle x}-1}{x}}$ $-$ $\displaystyle \large \lim_{x \to 0}{\normalsize \dfrac{\sin{x}}{x}}$

As per exponential limit rule, the limit of quotient of subtraction of one from natural exponential function by the variable as the variable approaches zero is equal to one. Similarly, the limit of quotient of sine of a variable by variable as the variable tends to zero is also equal to one as per trigonometric limit rule.

$= \,\,\,$ $e^3 \times 1$ $-$ $1$

$= \,\,\, e^3-1$

Latest Math Topics

Latest Math Problems

Email subscription

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.